Metabarcoding detection of Vibrio species in black-tailed gulls reveals seabirds as overlooked sentinels of coastal zoonotic risk in South Korea - Singeun Oh; Dewi Arinta; Buyanbadrakh Burenbaatar; Jun Ho Choi; Leon Kim; Du-Yeol Choi; Dongjun Kang; Arwa Shatta; Myung-hee Yi; Yoon Hee Cho; In-Yong Lee; Ju Yeong Kim (Environmental Research, 2026)

The impact of redox changes on uranium migration using a field tracer test and reactive transport modeling - In-Hee Cho; Suh-Ho Lee; In-Woo Park; Jaeyeon Kim; Won-Tak Joun; Kang-Kun Lee (Journal of Hazardous Materials, 2026)

Near-infrared light–responsive implantable module integrated into glaucoma drainage device for controlled antifibrotic drug therapy - Chang Hee Min; Young In Shin; Han Bi Ji; Soo Bin Yoon; Yeonseo Kim; Cho Rim Kim; Jae Hoon Han; Min Ji Kim; Myung Ju Kim; Eun Jung Kwon; Young Kook Kim; Ki Ho Park; et al. (Chemical Engineering Journal, 2026)

Future variability in groundwater-surface water interactions: Implications for streamflow and its components using SWAT-MODFLOW 6 and CMIP 6 projections - Suh-Ho Lee; Hye-Ji Kim; In-Hee Cho; Seong-Sun Lee; Hyemin Park; Youn-Tae Kim; MoonSu Kim; Kang-Kun Lee (Journal of Hydrology, 2026)

Enhancing CO2-to-CH4 conversion efficiency of TiO2 through synergistic morphology tuning, defect engineering, and heterojunction formation - Dongyun Kim; Kyuseok Lee; Young Ho Park; Junho Lee; Jeonghyeon Lee; Chaelin Shin; Hyeonjong Jeong; Chang-Hee Cho; G. Murali; Seung Jun Lee; Insik In; Su-Il In (Chemical Engineering Journal, 2026)

Seasonal and spatial distributions of polycyclic aromatic hydrocarbons in surface water of the Taehwa River in the largest industrial city in South Korea - In-Gyu Cho; Hye-Ok Kwon; Sung-Hee Seo; Joo-Yeon Oh; Eun-Jeong Park; Sung-Deuk Choi (Environmental Monitoring and Assessment, 2025)

Green solvent-based highly permeable PES membranes for virus filtration in bioprocesses - Chang-Hun Kim; Eunwoo Jung; In-Chul Kim; Mi-Hee Ryu; Jung-Hyun Lee; Youngbin Baek; Young Hoon Cho (Chemical Engineering Journal, 2025)

Chitosan-gallic acid conjugate edible coating film for perishable fruits - Cho Rok Lee; Su Jin Lee; Tae In Kim; Kiramage Chathuranga; Jong Soo Lee; Sangsik Kim; Min Hee Kim; Won Ho Park (Food Chemistry, 2025)

Concentration of docosahexaenoic acid from tuna oil via a two lipase-catalyzed reaction - Yejie Cho; Byung Hee Kim; Yangha Kim; In-Hwan Kim (Food Chemistry, 2024)

Polyhexamethylene guanidine phosphate induces pyroptosis via reactive oxygen species-regulated mitochondrial dysfunction in bronchial epithelial cells - Jun Young Park; Ji-Hee Kim; Chan Ho Park; Sung-Hwan Kim; In-Hyeon Kim; Won Gil Cho (Toxicology, 2024)

Sex, age, and species differences of perfluorooctanoic acid modeled by flow- versus permeability-limited physiologically-based pharmacokinetic models - Go-Wun Choi; Dong Wook Kang; Ju Hee Kim; Seok-jin Cho; Yong-Bok Lee; In-Ho Kwon; Hea-Young Cho (Toxicology, 2024)

Dynamic Ti3+ and In3+ dual active sites on In2TiO5 to enhance visible-light-driven gas-phase photocatalytic CO2 reduction - Niket S. Powar; Myeongjin Jang; Min Gyu Kim; Chaitanya B. Hiragond; Junho Lee; Eunhee Gong; Hwapyong Kim; Dongyun Kim; Jin-Woo Jung; Chang-Hee Cho; Tierui Zhang; Minho Kim; et al. (Chemical Engineering Journal, 2024)

In situ electrolyte replenishment with atmospheric pressure-chemical/electrochemical vapour deposition for molten carbonate fuel cells - Kab In Kim; Jae Kwan Bae; Emilio Audasso; Albert Won Cho; Young Bae Jun; Hyun Seo Park; Seong-Cheol Jang; Yong Soo Cho; Han Sung Kim; Sun-Hee Choi; Sung Pil Yoon (Chemical Engineering Journal, 2023)

Inverse opal-structured all-in-one water purification filter designed for the effective removal of multi-pollutants - Hee Jung Kim; Gill Sang Han; Jaesung Kim; Young Ju Kim; Jin Hyuk Choi; Jae Myeong Lee; Geon Woo Yoon; Hongshin Lee; In Sun Cho; Jaesang Lee; Hyun Suk Jung (Journal of Water Process Engineering, 2023)

A rice seed-specific glycine-rich protein OsDOR1 interacts with GID1 to repress GA signaling and regulates seed dormancy - Sooyeon Kim; Sun Mi Huh; Hay Ju Han; Gang Seob Lee; Yong-Sic Hwang; Mi Hyun Cho; Beom-Gi Kim; Ji Sun Song; Joo Hee Chung; Myung Hee Nam; Hyeonso Ji; Kyung-Hwan Kim; et al. (Plant Molecular Biology, 2023)

Synergistic role of hydrogen treatment and heterojunction in H-WO3-x/TiO2-x NT/Ti foil-based photoanodes for photoelectrochemical wastewater detoxification and antibacterial activity - Mahadeo A. Mahadik; In-Seon Hwang; Weon-Sik Chae; Hyun Hwi Lee; Sun Hee Choi; Min Cho; J.S. Jang (Chemosphere, 2023)

Improvement of germinability of lettuce seeds with drum-priming under high temperature condition - Jong-In Park; Dong-Myung Cho; Jeong-Hee Oh; Ju-Sung Cho; Nam-Jun Kang (Horticulture, Environment, and Biotechnology, 2022)

A Comparative Study of an Anti-Thrombotic Small-Diameter Vascular Graft with Commercially Available e-PTFE Graft in a Porcine Carotid Model - Kyo Seon Lee; Mukhammad Kayumov; Gladys A. Emechebe; Do-Wan Kim; Hwa-Jin Cho; Yun-Jin Jeong; Dong-Weon Lee; Jun-Kyu Park; Chan-Hee Park; Cheol-Sang Kim; Francis O. Obiweluozor; In-Seok Jeong (Tissue Engineering and Regenerative Medicine, 2022)
Background: We have designed a reinforced drug-loaded vascular graft composed of polycaprolactone (PCL) and polydioxanone (PDO) via a combination of electrospinning/3D printing approaches. To evaluate its potential for clinical application, we compared the in vivo blood compatibility and performance of PCL/PDO + 10%DY grafts doped with an antithrombotic drug (dipyridamole) with a commercial expanded polytetrafluoroethylene ( e -PTFE) graft in a porcine model. Methods: A total of 10 pigs (weight: 25–35 kg) were used in this study. We made a new 5-mm graft with PCL/PDO composite nanofiber via the electrospinning technique. We simultaneously implanted a commercially available e -PTFE graft ( n = 5) and our PCL/PDO + 10%DY graft ( n = 5) into the carotid arteries of the pigs. No anticoagulant/antiplatelet agent was administered during the follow-up period, and ultrasonography was performed weekly to confirm the patency of the two grafts in vivo . Four weeks later, we explanted and compared the performance of the two grafts by histological analysis and scanning electron microscopy (SEM). Results: No complications, such as sweating on the graft or significant bleeding from the needle hole site, were seen in the PCL/PDO + 10%DY graft immediately after implantation. Serial ultrasonographic examination and immunohistochemical analysis demonstrated that PCL/PDO + 10%DY grafts showed normal physiological blood flow and minimal lumen reduction, and pulsed synchronously with the native artery at 4 weeks after implantation. However, all e -PTFE grafts occluded within the study period. The luminal surface of the PCL/PDO + 10%DY graft in the transitional zone was fully covered with endothelial cells as observed by SEM. Conclusion: The PCL/PDO + 10%DY graft was well tolerated, and no adverse tissue reaction was observed in porcine carotid models during the short-term follow-up. Colonization of the graft by host endothelial and smooth muscle cells coupled with substantial extracellular matrix production marked the regenerative capability. Thus, this material may be an ideal substitute for vascular reconstruction and bypass surgeries. Long-term observations will be necessary to determine the anti-thrombotic and remodeling potential of this device.

Construction of full-length infectious cDNA clones of two Korean isolates of turnip mosaic virus breaking resistance in Brassica napus - Zheng-Xing Song; Eun-Young Seo; Wen-Xing Hu; Jong-Hyeon Jeong; Jae Sun Moon; Kang-Hee Kim; Won-Seob Eom; In-Sook Cho; John Hammond; Hyoun-Sub Lim (Archives of Virology, 2022)

Anti-inflammatory activity of palmitoylethanolamide ameliorates osteoarthritis induced by monosodium iodoacetate in Sprague–Dawley rats - Jae In Jung; Hyun Sook Lee; Young Eun Jeon; So Mi Kim; Su Hee Hong; Joo Myung Moon; Cho Young Lim; Yoon Hee Kim; Eun Ji Kim (Inflammopharmacology, 2021)
Novel treatment strategies are urgently required for osteoarthritis (OA). Palmitoylethanolamide (PEA) is a naturally occurring fatty acid amide with analgesic and anti-inflammatory effects. We aimed to examine its effect on OA and elucidate the molecular mechanism of actions in monosodium iodoacetate (MIA)-induced OA Sprague–Dawley rats. The experimental animals were divided into normal control group (injected with saline + treated with phosphate-buffered saline (PBS), NOR), control group (injected with MIA + treated with PBS, CON), 50 or 100 mg/kg body weight (BW)/day PEA-treated group (injected with MIA + treated with 50 or 100 mg of PEA/kg BW/day, PEA50 or PEA100), and positive control group (injected with MIA + treated with 6 mg of diclofenac/kg BW/day, DiC). The changes in blood parameters, body parameters, gene expression of inflammatory mediators and cytokines, knee thickness, and joint tissue were observed. Oral administration of PEA had no adverse effects on the BW, liver, or kidneys. PEA reduced knee joint swelling and cartilage degradation in MIA-induced OA rats. The serum levels of leukotriene B4, nitric oxide, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and prostaglandin E2 considerably reduced in the PEA100 group compared with those in the CON group. In the synovia of knee joints, the mRNA expression of iNOS , 5-Lox , Cox-2 , Il-1β , Tnf-α , and Mmp-2 , -3 , -9 , and -13 apparently increased with MIA administration. Meanwhile, Timp-1 mRNA expression apparently decreased in the CON group but increased to the normal level with PEA treatment. Thus, PEA can be an effective therapeutic agent for OA.

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Considerations in the Development of Small-Diameter Vascular Graft as an Alternative for Bypass and Reconstructive Surgeries: A Review - Francis O. Obiweluozor; Gladys A. Emechebe; Do-Wan Kim; Hwa-Jin Cho; Chan Hee Park; Cheol Sang Kim; In Seok Jeong (Cardiovascular Engineering and Technology, 2020)

Effects of the DNA repair inhibitors, cytosine arabinoside and 3-aminobenzamide, on the frequency of radiation-induced micronuclei, nuclear buds, and nucleoplasmic bridges - Yoon Hee Cho; Yang Jee Kim; Sunyeong Lee; Kyung-in Joung; Hai Won Chung; Sunmi Kim; Su Young Kim (Genes & Genomics, 2020)

Amino acid differences in the N-terminal half of the polyprotein of Chinese turnip mosaic virus isolates affect symptom expression in Nicotiana benthamiana and radish - Wen-Xing Hu; Eun-Young Seo; In-Sook Cho; Jung-Kyu Kim; Hye-Kyoung Ju; Ik-Hyun Kim; Go-Woon Choi; Boram Kim; Chun-Hee Ahn; Leslie L. Domier; Sang-Keun Oh; John Hammond; et al. (Archives of Virology, 2019)

Hymenobacter pomorum sp. nov., Isolated from Apple Orchard Soil - Leonid N. Ten; Weilan Li; Seung-Yeol Lee; In-Kyu Kang; Young-Je Cho; Myung Kyum Kim; Hee-Young Jung (Current Microbiology, 2019)

Individualized metabolic profiling stratifies pancreatic and biliary tract cancer: a useful tool for innovative screening programs and predictive strategies in healthcare - Jun Hwa Lee; Seung Eun Yu; Kyung-Hee Kim; Myung Hyun Yu; In-Hye Jeong; Jae Youl Cho; Sang-Jae Park; Woo Jin Lee; Sung-Sik Han; Tae Hyun Kim; Eun Kyung Hong; Sang Myung Woo; et al. (EPMA Journal, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Whitening and anti-wrinkle activities of ferulic acid isolated from Tetragonia tetragonioides in B16F10 melanoma and CCD-986sk fibroblast cells - Hye-Jin Park; Jun-Hyo Cho; Shin-Hyub Hong; Dong-Hee Kim; Hee-Young Jung; In-Kyu Kang; Young-Je Cho (Journal of Natural Medicines, 2018)

Urinary 6β-Hydroxycortisol/Cortisol Ratio Most Highly Correlates With Midazolam Clearance Under Hepatic CYP3A Inhibition and Induction in Females: A Pharmacometabolomics Approach - Kwang-Hee Shin; Li Young Ahn; Man Ho Choi; Ju-Yeon Moon; Jieon Lee; In-Jin Jang; Kyung-Sang Yu; Joo-Youn Cho (The AAPS Journal, 2016)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Chondrogenic potential and anti-senescence effect of hypoxia on canine adipose mesenchymal stem cells - Jienny Lee; Jeong Su Byeon; Keum Sil Lee; Na-Yeon Gu; Gyeong Been Lee; Hee-Ryang Kim; In-Soo Cho; Sang-Ho Cha (Veterinary Research Communications, 2016)

Osteogenic differentiation of human mesenchymal stem cells promoted by the crude extracts of the mixture of Cortex mori radicis, Patrinia saniculaefolia - Koh-Woon Kim; In-Seung Lee; Won-Jae Lee; Jiyoung Park; Won Seok Chung; Jae-Heung Cho; Sung-Lim Lee; Hyeung-Jin Jang; Seok-Hee Chung (Molecular & Cellular Toxicology, 2015)

Genomic detection and characterization of a Korean isolate of Little cherry virus 1 sampled from a peach tree - Seungmo Lim; Davaajargal Igori; Ran Hee Yoo; Fumei Zhao; In-Sook Cho; Gug-Seoun Choi; Hyoun-Sub Lim; Su-Heon Lee; Jae Sun Moon (Virus Genes, 2015)

Inhibition effect of phenyl compounds from the Oryza sativa roots on melanin production in murine B16-F10 melanoma cells - Jin-Gyeong Cho; Jeongran Huh; Rak-Hun Jeong; Byeong-Ju Cha; Sabina Shrestha; Dong-Geol Lee; Hee-Cheol Kang; Ji-Young Kim; Nam-In Baek (Natural Product Research, 2015)

Genome-wide association analysis to identify SNP markers affecting teat numbers in an F2 intercross population between Landrace and Korean native pigs - Jae-Bong Lee; Eun-Ji Jung; Hee-Bok Park; Shil Jin; Dong-Won Seo; Moon-Suck Ko; In-Cheol Cho; Jun-Heon Lee; Hyun-Tae Lim (Molecular Biology Reports, 2014)

Analysis of S-locus and expression of S-alleles of self-compatible rapid-cycling Brassica oleracea ‘TO1000DH3’ - Jung Hee-Jeong; Ahmed Nasar Uddin; Park Jong-In; Thamilarasan Senthil Kumar; Kim Hye-Ran; Cho Yong-Gu; Nou Ill-Sup (Molecular Biology Reports, 2014)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

The anti-inflammatory effects of Alisma herb extract on allergic asthma mouse model - Min-Hee Shin; Yu Jin Park; Ki-Suk Kim; Dong Hyuk Cho; In Joon Uh; Kang-Hoon Kim; In Jin Ha; Won-Seok Chung; Hee-Jae Jung; Sung-Ki Jung; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2014)

Triterpenoids from Fragaria ananassa calyx and their inhibitory effects on melanogenesis in B16-F10 mouse melanoma cells - Na-Young Song; Jin-Gyeong Cho; Dongmoon Im; Dae-Young Lee; Qian Wu; Woo-Duck Seo; Hee Cheol Kang; Youn-Hyung Lee; Nam-In Baek (Natural Product Research, 2013)

Phellinus baumii ethyl acetate extract alleviated collagen type II induced arthritis in DBA/1 mice - Taddesse Yayeh; Whi Min Lee; Dukhwan Ko; Seung-Choon Park; Jae Youl Cho; Hwa-Jin Park; In-Kyoung Lee; Seung-Hyung Kim; Seung-Bok Hong; Suk Kim; Bong-Sik Yun; Man Hee Rhee (Journal of Natural Medicines, 2013)

Identification of molecular mechanism controlling P34 gene expression in soybean - Sung Cheol Koo; Jun Su Seo; Min Jung Park; Hyun Min Cho; Mi Suk Park; Cheol Woo Choi; Wook-Hun Jung; Kyoung Hee Lee; Byung Jun Jin; Seok Hyeon Kim; Sang In Shim; Jung-Sung Chung; et al. (Plant Biotechnology Reports, 2013)

Comparative analysis of physicochemicals and antioxidative properties in new red rice (Oryza sativa L. cv. Gunganghongmi) - Woo Duck Seo; Jun Young Kim; You-Chun Song; Jun-Hyun Cho; Ki Chang Jang; Sang-Ik Han; Ji-Eun Ra; Seong-Hwan Oh; Hyeon-Jung Kang; Byung-Joo Kim; Nam-In Baek; Rak-Hun Jeong; et al. (Journal of Crop Science and Biotechnology, 2013)

Association of the gene encoding stearoyl-CoA desaturase (SCD) with fatty acid composition in an intercross population between Landrace and Korean native pigs - Dyah Maharani; Hee-Bok Park; Jae-Bong Lee; Chae-Kyoung Yoo; Hyun-Tae Lim; Sang-Hyun Han; Sung-Soo Lee; Moon-Suck Ko; In-Cheol Cho; Jun-Heon Lee (Molecular Biology Reports, 2013)

A missense mutation (c.1963A<G) of the complementary component 2 (C2) gene is associated with serum Ca++ concentrations in pigs - Jae-Bong Lee; Chae-Kyoung Yoo; Eun-Ji Jung; Jung-Hye Hwang; Bo-Young Seo; Byeong-Woo Kim; Hyun-Tae Lim; Jung-Gyu Lee; In-Cheol Cho; Hee-Bok Park (Molecular Biology Reports, 2012)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

QTL analysis of back fat thickness and carcass pH in an F2 intercross between Landrace and Korean native pigs - Chae-Kyoung Yoo; Hyun-Tae Lim; Sang-Hyun Han; Sung-Soo Lee; Moon-Suck Ko; Taeyoung Kang; Jun Heon Lee; Hee-Bok Park; In-Cheol Cho (Molecular Biology Reports, 2012)

Characterization of phenotypic variants of Clavibacter michiganensis subsp. michiganensis isolated from Capsicum annuum - Kyu-Ock Yim; Hyok-In Lee; Jung-Hee Kim; Seung-Don Lee; Jung-Hee Cho; Jae-Soon Cha (European Journal of Plant Pathology, 2012)

OsREL2, a rice TOPLESS homolog functions in axillary meristem development in rice inflorescence - Yerim Kwon; Si-in Yu; Joo-hyuk Park; Ying Li; Jin-Hee Han; Hemasundar Alavilli; Jung-Il Cho; Tae-Houn Kim; Jong-Seong Jeon; Byeong-ha Lee (Plant Biotechnology Reports, 2012)

Phellinus baumii ethyl acetate extract inhibits lipopolysaccharide-induced iNOS, COX-2, and proinflammatory cytokine expression in RAW264.7 cells - Taddesse Yayeh; Won Jun Oh; Seung-Choon Park; Tae-Hwan Kim; Jae Youl Cho; Hwa-Jin Park; In-Kyoung Lee; Sang-Keun Kim; Seung-Bok Hong; Bong-Sik Yun; Man Hee Rhee (Journal of Natural Medicines, 2012)

QTL analysis of fruit length using rRAMP, WRKY, and AFLP markers in chili pepper - Heung-Ryul Lee; Ki-Taek Kim; Hyoun-Joung Kim; Jung-Heon Han; Jeong-Ho Kim; Seon-In Yeom; Hyun Jung Kim; Won-Hee Kang; Jinxia-Shi; Soung-Woo Park; Ik-Hyun Bae; Semin Lee; et al. (Horticulture, Environment, and Biotechnology, 2011)

Gene flow from herbicide-tolerant GM rice and the heterosis of GM rice-weed F2 progeny - Young Jin Chun; Dae In Kim; Kee Woong Park; Hyo-Jeong Kim; Soon-Chun Jeong; Ju Hee An; Kang Hyun Cho; Kyoungwhan Back; Hwan Mook Kim; Chang-Gi Kim (Planta, 2011)

Isolation of the groESL cluster from Vibrio anguillarum and PCR detection targeting groEL gene - Dong-Gyun Kim; Yu-Ri Kim; Eun-Young Kim; Hyun Min Cho; Sun-Hee Ahn; In-Soo Kong (Fisheries Science, 2010)

Doxycycline is Neuroprotective Against Nigral Dopaminergic Degeneration by a Dual Mechanism Involving MMP-3 - Yuri Cho; Hyo Jin Son; Eun-Mee Kim; Ji Hyun Choi; Sung Tae Kim; In Jung Ji; Dong Hee Choi; Tong H. Joh; Yoon Seong Kim; Onyou Hwang (Neurotoxicity Research, 2009)

Assessment of Gene Flow from Genetically Modified Anthracnose-Resistant Chili Pepper (Capsicum annuum L.) to a Conventional Crop - Chang-Gi Kim; Dae In Kim; Hyo-Jeong Kim; Ji Eun Park; Bumkyu Lee; Kee Woong Park; Soon-Chun Jeong; Kyung Hwa Choi; Joo Hee An; Kang-Hyun Cho; Young Soon Kim; Hwan Mook Kim (Journal of Plant Biology, 2009)

Prevalence and molecular characterization of meq in feather follicular epithelial cells of Korean broiler chickens - Jung-Won Kang; Sun-Hee Cho; In-Pil Mo; Dong-Woo Lee; Hyuk-Joon Kwon (Virus Genes, 2007)

Knockout of a starch synthase gene OsSSIIIa/Flo5 causes white-core floury endosperm in rice (Oryza sativa L.) - Nayeon Ryoo; Chul Yu; Cheon-Seok Park; Moo-Yeol Baik; In Myoung Park; Man-Ho Cho; Seong Hee Bhoo; Gynheung An; Tae-Ryong Hahn; Jong-Seong Jeon (Plant Cell Reports, 2007)

A rice dehydration-inducible SNF1-related protein kinase 2 phosphorylates an abscisic acid responsive element-binding factor and associates with ABA signaling - Min-Ju Chae; Jung-Sook Lee; Myung-Hee Nam; Kun Cho; Ji-Yeon Hong; Sang-A Yi; Seok-Cheol Suh; In-Sun Yoon (Plant Molecular Biology, 2006)

Biflavonoids inhibited phosphatase of regenerating liver-3 (PRL-3) - Sung-Kyu Choi; Hyun-Mi Oh; Su-Kyung Lee; Dae Gwin Jeong; Seong Eon Ryu; Kwang-Hee Son; Dong Cho Han; Nack-Do Sung; Nam-In Baek; Byoung-Mog Kwon (Natural Product Research, 2006)

Surfactin C inhibits the Lipopolysaccharide-induced Transcription of Interleukin-1β and Inducible Nitric Oxide Synthase and Nitric Oxide Production in Murine RAW 264.7 Cells - Mi-Hyun Hwang; Jong-Hwan Lim; Hyo-In Yun; Man-Hee Rhee; Jae-Youl Cho; Walter H. Hsu; Seung-Chun Park (Biotechnology Letters, 2005)

Expression of Interferon Inducible Genes Following Hantaan Virus Infection as a Mechanism of Resistance in A549 Cells - Jae-Hwan Nam; Kyung-A Hwang; Cheong-Hee Yu; Tae-Hoon Kang; Jae-Young Shin; Woo-Young Choi; In-Beom Kim; Young-Ran Joo; Hae-Wol Cho; Keun-Yong Park (Virus Genes, 2003)